Black Greek-letter organizations 2.0 : new directions in the study of African American fraternities and sororities - Hughey, Matthew W. (Matthew Windust); Parks, Gregory, 1974- (University Press of Mississippi, 2011)
At the turn of the twentieth century, black fraternities and sororities, also known as black Greek-letter organizations (BGLOs), were an integral part of the top ten percent of the black community that would serve as a cadre of educated, upper-class, motivated individuals who acquired the professional credentials, skills, and capital to assist the race to attain socio-economic parity. Today, however, BGLOs struggle to find their place and direction in a world drastically different from the one that witnessed their genesis.